A Review of Breast Cancer Treatment Modalities in Uganda- an Appraisal of the Breast Cancer Diagnostic Process, Regulatory Approval and Supply System of Standardized Anti-Breast Cancer Medicines - Lutoti, Stephen; Kamba, Pakoyo F.; Katuura, Esther; Wangalwa, Raphael; Mtewa, Andrew; Ogwang, Patrick E.; Mukonzo, Jackson; Mugume, Noleb Mugisha (International Journal of Advanced Research, 2020)
Breast cancer is the leading cause of cancer death among women and the third incident cancer in the world, contributing 1.7 million of the 17.2 million annual incident cancer cases. For Uganda, breast cancer is the third incident cancer and fourth cause of cancer related deaths. The Uganda cancer treatment guidelines focuses on treatment of five cancers that constitute 60% of the national cancer burden, namely; Kaposi sarcoma, cancer of cervix, prostate cancer, esophageal cancer and breast cancer. We present a review of the treatment modalities of breast cancer based upon Uganda‟s treatment guidelines as well as documented clinical practices. Diagnosis of breast cancer is delayed in most patients and based on clinical evaluation of risk factors, clinical manifestations and laboratory investigations. Staging is based on The American Joint Committee on Cancer TNM system. Surgery, radiotherapy and chemotherapy are the recommended treatment options administered singly or in combination with each other depending on the stage of breast cancer at the time of diagnosis. We found 21 standard treatment regimens based on 17 drug molecules have been recommended for various breast cancers. Seven of these molecules are among 13 other cytotoxic drugs approved by WHO as essential antibreast cancer medicines. 39 brands of these drug molecules were found registered by the National drug Authority in Uganda as of 23rdAugust 2018, accounting for 0.01% of all the registered drugs for human use in Uganda.
Keywords: Breast Cancer; Chemotherapy; Radiotherapy; Cytotoxic; Surgery